Subclinical systolic dysfunction in children with steroid-resistant nephrotic syndrome identified by speckle tracking echocardiography - Mohamed Hashem Mahgoob; Amr Mostafa Setouhi (BMC Pediatrics)
Abstract Background Steroid resistant nephrotic syndrome (SRNS) is a clinical phenotype of nephrotic syndrome (NS) that does not respond to steroid therapy and usually results in kidney failure. The aim of this study was to determine whether children with SRNS have subclinical left ventricular systolic dysfunction and, if so, to identify the risk factors for myocardial involvement in those children. Methods This prospective case-control study included of 35 children with SRNS, 40 children in the healthy control group, and 40 children with NS during the initial episode as the diseased control group. Conventional echocardiography, tissue Doppler imaging (TDI), and speckle tracking echocardiography (STE) were performed on all the studied children. Results No statistically significant difference in conventional echocardiography’s parameters were detected between the patient and control groups. TDI revealed that the E/E′ ratio was significantly greater in the SRNS group than in both the healthy and diseased control groups (P = 0.001). The left ventricle global longitudinal strain (LV GLS) was markedly lower in children with SRNS than in healthy controls and NS patients (the diseased controls) (P = 0.001). Multiple binary regression analysis for the predictors of systolic dysfunction in SRNS patients revealed that the serum albumin is the only variable that predicts systolic dysfunction in these children. Conclusions Subclinical systolic and diastolic LV dysfunction should be screened in NS especially SRNS children.